Systematic Literature Review on Web Applications for Medical Attention and Medical Appointments - Alexander AGUILAR-CHÁVEZ; Jeshuá BANDA-BARRIENTOS; Javier GAMBOA-CRUZADO; Norma GÁLVEZ-DÍAZ; Liset RODRIGUEZ BACA; Guillermo PAUCAR-CARLOS; Carlos ARROYO-PÉREZ (Communications of International Proceedings, 2020)
Today, healthcare systems have a great wealth of information about patients. This has a direct impact on the way people seek information and care. The objective of this research is to provide a systematic literature review (SLR) of different studies that have been carried out since 2015 regarding the development of web applications in different areas of healthcare. Further, we provide a comprehensive statistical analysis, and specifically, we extracted 70 journal articles published between the years 2015 and 2020. The results provided in this document have enabled us to answer the questions posed and led us to conclude that web applications are necessary in medical systems. This is because such applications facilitate rapid access to essential patient data to any healthcare professional, thereby avoiding loss of data, delays in treatment while requesting information, and duplication of information.
Keywords: Medical Care; Medical Appointment; Web Application; Methodology; Scrum